(untitled) (The Conference Hub, 2025)
This article discusses the pressing issues of developing altruism among youth in contemporary society. It explores the significance of altruistic behavior in fostering social cohesion, empathy, and community engagement. The paper examines various factors influencing the development of altruism, including family upbringing, educational practices, and social media impact. Additionally, it highlights effective strategies and programs that can be implemented to promote altruistic values among young people. The findings suggest that nurturing altruism is essential for building a more compassionate and harmonious society.